PELAKSANAAN PERATURAN DAERAH NOMOR 10 TAHUN 2009 TENTANG USAHA PERIKANAN DI KABUPATEN KARIMUN (STUDI TETANG PERIZINAN USAHA PERIKANAN DI UNIT PELAKSANAAN TEKNIS PERIKANAN KUNDUR, KABUPATEN KARIMUN): (Studi Tetang Perizinan Usaha Perikanan di Unit Pelaksanaan Teknis Perikanan Kundur, Kabupaten Karimun) - Asrul muhayat; Ica Trifiwidyana; Ardi Putra (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
ABSTRACT Fishery is one of the marine natural resources owned by Indonesia, the utilization of fishery resources is carried out by means of fishery business. The implementation of fisheries business must pay attention to its sustainability so that it is not carried out excessively and has a good impact on the surrounding environment. Karimun Regency is an area that has abundant fishery resources. concerning fishery business has been regulated in the Karimun Regency Regional Regulation Number 10 of 2009 concerning Fishery Business. One of them is licensing. In this study, to find out about the implementation of regional regulations regarding fishery business licensing and the Government and regional fisheries business actors work together in finding solutions to the obstacles that occur in the fisheries business licensing process. By using descriptive-analytical method associated with the theory and practice of implementing positive law. In the implementation of licensing there are obstacles such as profile data, and inappropriate data matching by business actors. The conclusion in this study is that in implementing policies, obstacles and efforts to overcome government problems applying submissions for fishery business permits can be accessed online in the form of the ARAH-KAN application. Keywords: licensing; fishery business; karimun district